THE MODEL FOR CONTINUOUS PROFESSIONAL DEVELOPMENT OF ADDITIONAL EDUCATION TEACHERS: DESIGN EXPERIENCE IN THE REGIONAL DOMAIN - Fadeeva, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The mainstreaming of the additional education for children requires the training of the teaching staff capable of effectively developing the creative urges and gifts of pupils through the free choice of diverse activities. Additional education specialists should not only professionally know and have a good command of their subject, which supports children’s hobbies, but they shall also act as a catalyst for the development of the individual’s motivational potential, professional self-determination and as a long-term result they shall modify the innovative resource of society. Nevertheless, a teacher being a competent specialist in a certain subject domain such as theater and musical performance, aircraft modeling and robotics, powerlifting and football may not have sometimes the required knowledge and skills for the child's personality education and for designing expected educational results.The need for the scientific and methodological support to the professional development of the teaching staff in the additional education system has evoked the decision to elaborate a conceptually new model of training for this category of specialists, thus, having made it the purpose of the study. The novelty of the study was the fact that the said model was based on the personified nature of the choice of the teachers’ educational trajectory. It appeared to be a common multi-level structure combining diverse fields and forms of advanced training and retraining of additional education specialists. In addition to design and modeling methods there were applied in the study the methods of empirical research, interrogation and questioning, data analysis and generalization. The elaborated and implemented model for supporting the professional development of the teaching staff enabled to systematize and structure the training of additional education specialists in the regional domain. The practical relevance of the model for the continuous professional development was determined by its possible use also in the post-graduate education in another territory.